Inspectorate Auditor Performance Improvement Reference - Budi Rismayadi (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
Auditor performance can not be separated from the behavior of auditors in carrying out their duties. This study examines the relationship between professionalism, leadership style, organizational commitment, and work motivation on auditor performance. The research approach used in this study is a quantitative descriptive approach. This study involved 41 auditors at the Karawang Regency Inspectorate. The data analysis technique in this study used Partial Least Square (PLS). The study results found that professionalism positively and significantly affected auditor performance. There is no significant effect between leadership style on auditor performance. There is a significant positive effect between organizational commitment to the auditor's performance and the auditor's work motivation having a positive impact on the auditor's performance. The results of this study illustrate that this indicates that the auditor is more professional in his work and has the motivation to perform specific tasks in achieving a goal. The organization is not wholly and part of those who work as auditors. Auditors who have reason in carrying out their duties can provide good results in carrying out their responsibilities because basis can provide enthusiasm that will affect the performance of auditors.